Prenatal diagnosis and genetic etiology analysis of talipes equinovarus by chromosomal microarray analysis - Xiaorui Xie; Baojia Huang; Linjuan Su; Meiying Cai; Yuqin Chen; Xiaoqing Wu; Liangpu Xu (BMC, 2023)
Abstract Background With the advancement of molecular technology, fetal talipes equinovarus (TE) is believed to be not only associated with chromosome aneuploidy, but also related to chromosomal microdeletion and microduplication. The study aimed to explore the molecular etiology of fetal TE and provide more information for the clinical screening and genetic counseling of TE by Chromosomal Microarray Analysis (CMA). Methods This retrospectively study included 131 fetuses with TE identified by ultrasonography. Conventional karyotyping and SNP array analysis were performed for all the subjects. They were divided into isolated TE group (n = 55) and complex group (n = 76) according to structural anomalies. Results Among the total of 131 fetuses, karyotype analysis found 12(9.2%) abnormal results, while SNP array found 27 (20.6%) cases. Trisomy 18 was detected most frequently among abnormal karyotypes. The detection rate of SNP array was significantly higher than that of traditional chromosome karyotype analysis (P < 0.05). SNP array detected 15 (11.5%) cases of submicroscopic abnormalities that karyotype analysis did not find. The most common CNV was the 22q11.2 microdeletion. For both analyses, the overall detection rates were significantly higher in the complex TE group than in the isolated TE group (karyotype: P < 0.05; SNP array: P < 0.05). The incremental yield of chromosomal abnormalities in fetuses with unilateral TE (22.0%) was higher than in fetuses with bilateral TE (19.8%), but this difference was not statistically significant (P > 0.05). Abnormal chromosomes were most frequently detected in fetuses with TE plus cardiovascular system abnormalities. Conclusion Fetal TE is related to chromosomal microdeletion or microduplication. Prenatal diagnosis is recommended for fetuses with TE, and CMA testing is preferred. CMA can improve the detection rate of chromosomal abnormalities associated with fetal TE, especially in pregnancies with complex TE.